Limited Effect of CpG ODN in Preventing Type 1 Diabetes in NOD Mice - Lee, Byong Jun (Yonsei University College of Medicine, 2005)
Type 1 diabetes is considered as Th1 cell mediated autoimmune disease and the suppression of Th1 cells or the activation of Th2 cells has been regarded as a plausible immunologic intervention for the prevention of type 1 diabetogenesis in a rodent model. CpG ODN is an immunostimulatory sequence primarily present in bacterial DNA, viral DNA and BCG. CpG ODN is conventionally classified as a Th1 cell activator, which has been clinically applied to cancer, allergy and infectious disease. Recently, there was a promising report of that CpG ODN administration suppressed the development of type 1 diabetes in NOD mice by inducing Th2 cell mediated cytokine. However, the antidiabetogenic effect of CpG ODN on NOD mice is controversial. Thus, two studies were serially undertaken with various kinds of CpG motif to find a more optimal sequence and administration method. In the first study, CpG ODN was vaccinated four times and pancreatic inflammation and the quantity of serum insulin subsequently evaluated. In the second study, the amounts of IFN γ and IL-4 in sera were measured as representative cytokines of Th1 and Th2 cells, respectively. As a result, vaccination or continuous injection of CpG ODN failed to show a preventive effect on type 1 diabetogenesis in NOD mice. Structural differences of CpG ODN also had no affect on the result. CpG ODN also consistently showed affect on the pancreatic pathology. The productions of IFN and IL-4 were γ detected only in the K and D type CpG ODN administration groups. Comparison of the two cytokines leads to the conclusion that CpG ODN generated a Th1-weighted response in both study groups. It was assumed that CpG ODN failed to produce Th2-weighted cytokine milieu, which can overcome the genetically determined phenotype of NOD mice. Given these results, it was concluded that the immunotherapeutic application of CpG ODN on Type 1 diabetes had clear limitations.